Wildlife and people the human dimensions of wildlife ecology - Gray, Gary G. (Environment and the human condition, 1993)
"Wildlife and People focuses on the human aspect of the animal-habitat-human triad, providing an introduction to virtually every discipline - from anthropology and history to socioeconomics - included in the human dimensions of wildlife ecology." "Gary Gray maintains that the most fruitful approach to wildlife ecology grants coequality to wild animal population biology, the ecology and management of wildlife habitats, and the disciplines that consider wildlife in relation to human culture. He concentrates on socioeconomic aspects of habitat-animal-human interactions in a broad time-space-species perspective, examining topics ranging from aboriginal human-wildlife relationships to consumptive uses of wildlife and wildlife law, policy, and administration."--BOOK JACKET.